Inflation targeting: How the Federal Reserve abandoned 'honest money' for a perpetual inflation tax - Paul H. Kupiec (American Enterprise Institute (AEI), 2021)
There was a time when the Federal Reserve believed that honest money—i.e., a stable price level— was essential for achieving full employment. Today, retired Fed officials are recommending that the Federal Open Market Committee (FOMC) target 3-percent inflation. They argue that a 3 percent inflation target would limit the risk of deflation and create large transitory reductions in unemployment and cumulative gains equal to 50 percent of GDP over a 15-year period. I review the evidence on deflation, the Phillips curve relationship that promises to deliver sizable output gains, the FOMC's historical experience with Phillips curve models, and how the FOMC's monetary strategy evolved from policy coordination, to price stability, to implicit, and finally to explicit inflation targeting. I analyze historically important factors that may prevent the realization of the hypothetical gains created by increasing the inflation rate target and summarize the literature that describes the costs and benefits of inflation. Finally, I provide estimates of the additional inflation tax revenue generated by increasing the FOMC's inflation target from 2 to 3 percent and show that, at a minimum, if the hypothetical gains were realized, more than 61 percent of the output gains would accrue to the Federal government. If output gains are not forthcoming, the change in the inflation target will still transfer trillions of dollars of inflation tax revenue from the public to the federal government and impose additional welfare costs that come with higher inflation.
Keywords: A; 330; Federal Open Market Committee; Federal Reserve; Gross Domestic Product (GDP); Inflation